Pelaksanaan Hak Pekerja Outsourcing Ditinjau dari Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan pada Bank Rakyat Indonesia Cabang Kalabahi - Faradila Umayyah; Siti Ramlah Usman; Helsina Fransiska Pello (International Forum of Researchers and Lecturers, 2024)
Regional levies are a form of community participation in implementing regional autonomy. Regional levies are an important source of regional income to fund government administration and regional development. The problem faced by each region in general is that the collection of levies which is a component of Original Regional Income (PAD) has not been maximized. This researcher aims to understand the management of parking fees in increasing the regional income of the city of Kupang and the efforts made by the regional government of the city of Kuapang in optimizing the receipt of parking fees. This type of research is empirical research, using a qualitative approach method, where the researcher describes data from the results of observations and research that has been carried out in Kupang City. The data collection techniques used are interviews and observations, then descriptive analysis is carried out. Parking lot management to increase local revenue is carried out through planning, organizing, activating/implementing and supervising or controlling activities. Efforts to increase local revenue through parking fees by establishing regulations and policies relating to parking fees, enforcing regulations, increasing supervision, educating the public, and evaluating the management of parking fees. Suggestions for the government to pay more attention to regional levies, especially Kupang City regional parking levies, in making regulations, enforcing regulations and increasing awareness of parking fees and providing education to the community as well as periodic evaluations for parking managers and officers so that they are obedient in carrying out their duties in accordance with applicable regulations. with a full sense of responsibility, and for the community to comply with regulations regarding regional levies, especially Kupang City regional parking levies to increase local revenue.